Knowledge-based development as a new economic culture - Francisco Javier Carrillo (Journal of Open Innovation: Technology, Market, and Complexity, 2015)
This is a theoretical research paper that aims to make the case for the major cultural evolution underlying the transition from industrial to knowledge societies. The approach followed consists of a theoretical analysis of the redefinition of production factors as well as the output variables to characterize and measure social worth. A major emphasis is placed upon economy as culture, one where not just financial and material capital, but all worthy value dimensions are given due consideration. As a result, knowledge-based value is characterized through represented experience, i.e., acquired symbols and preference criteria. The nature of k-based as opposed to material-based economics is central to this discussion. The paper concludes that a new economic culture shall evolve in parallel to the emergence of knowledge cities and societies. The "knowledge" attribute of knowledge cities relies on the capacity to balance all societal values into an equitable and sustainable dynamic equilibrium. The background section provides an introduction to the evolving concept of knowledge-based, in contrast to the prevailing material-based paradigm of industrial culture. The approach section explores the behavioral and social bases of such distinction. The discussion section concentrates on the economic foundations of knowledge-based value generation. Finally, the conclusions draw on the implications of the above discussion for economic science and the emerging knowledge-based culture.
Keywords: 650; Material-based; Industrial culture; Knowledge-based; Knowledge-based value systems; Capital systems; Knowledge city; Knowledge-based development (KBD); Knowledge culture; Knowledge society; Knowledge economy